The Benefits Case for Diversity in Nonprofits - Glazerman, Allan H. (Advances in Social Sciences Research Journal, 2025)
In this conceptual paper, I argue that there is, in nonprofits, a case comparable to the “business case” for diversity in for-profit organizations. The primary goal of nonprofits is not profit maximization, but the achievement of social benefit or the advancement of the public good through their mission. I contend that, just as there is a case that diversity benefits the goals of for-profit organizations, there is a comparable case that diversity advances the goals of nonprofits as well. We might call it the benefits case for diversity in nonprofits. I distinguish between direct and indirect benefits. In for-profit organizations, diversity has been shown to increase flexibility, enhance creativity and innovation, and improve decision-making and problem-solving. These direct benefits, when applied to areas such as cost control, marketing, and recruitment, lead to improved outcomes—producing indirect benefits and, ultimately greater profits. Similarly, in nonprofits, diversity generates comparable direct benefits, which translate into greater social impact through mission fulfillment. In one case, they lead to higher profitability and greater shareholder wealth; in the other, they contribute to greater social impact through mission fulfillment. The disanalogy lies in measurement: for-profit organizations have a single quantifiable metric—namely, profit—which allows for a direct correlation between diversity and organizational success. Nonprofits lack a single universal metric. However, they do have various indicators (for example, membership growth and dollars raised) that can be used to measure and track success and progress toward fulfilling their individual missions.